Relationship between higher education and basic education: collective work, protagonism and innovation in the physical education subproject of the pedagogical residency program at the Federal University of Pará (Research, Society and Development, 2022)
The research aims to analyze how the University/School relationship, the collaboration/protagonism and innovation affect the quality of the work developed by Physical Education in the Pedagogical Residency Program (PRP) of the Federal University of Pará (UFPA) and, consequently, in basic education in the Pará Amazon. The subjects are staff and preceptors of three field schools of the Physical Education subproject of the PRP of UFPA, besides residents, undergraduate students of Physical Education. The results show that, processually, an articulated relationship between University and School in the PRP collaborates to the emergence of collaborative work which, in turn, provides the emergence of plural and innovative pedagogical activities, the result of the protagonism assumed by preceptor teachers and residents in the program. In the schools of Pará served by the Physical Education subproject investigated, this process favors the emergence of educational possibilities with local knowledge and the critical incorporation of the phenomena and objects of Physical Education by basic education students.